Implementation Of The Use Of AIS On MSMEs In Facing The Industrial Revolution 4.0 - Almira, Rahma; Depi, Sri; Pontoh, Grace Theresia; Mediaty, Mediaty (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
The existence of an Accounting Information System (SIA) in a Micro, Small and Medium Enterprise (MSME) is useful for compiling reports needed by MSMEs to produce efficient and valid reports. Seeing this phenomenon, in this article the researcher intends to find out more about how to implement an Accounting Information System (AIS) in the era of the industrial revolution 4.0 in MSMEs. The method used in this research is the Systematic Literature Review (SLR) which examines previous studies. The data analysis used in this study was in the form of 20 selected articles from 2017-2022 in the Google Scholar and Elsevier databases. Based on the results of the study, it was found that there are five important roles of accounting information systems in digital form that play a role in improving the performance of MSMEs, including (1) organizational performance, (2) customer service, (3) reporting on buying and selling transaction activities, (4) improvement financial reporting, and (5) Performance improvement related to decision making for all parties with authority. The limitations in this study are the lack of international articles that discuss related topics and the limited international articles that make SMEs the object of research.